The new luxury is not gold, it is green: communicating sustainability within the luxury market: the case of the brazilian luxury fashion brand Osklen - Attili, Isabella Lazarini Silveira (2018)
Sustainability is not just a trend. It is a fact and it is irreversible. Over thousands of years the human being has been taking action without taking into consideration the damage done to the Earth. In an unbridled search for growth and profits, companies have explored nature to its limits and we are currently suffering the consequences of these acts. However, the theme of sustainability has come into vogue trying to help reverse this situation and is no longer just an option once people are demanding this from brands. Becoming sustainable is a must for companies that want to continue to operate in the market and for that, make use of Corporate Social Responsibility practice is an alternative. Regarding the fashion market, especially the luxury sector, they carry with them the burden of one of the biggest pollutants of the environment and therefore, one of the most charged to promote changes in their values, production methods and message transmitted to the consumer. And it was in this wave of awareness that Osklen, a Brazilian luxury fashion brand founded by Oskar Metsavaht, took its first steps towards becoming one of the pioneers of sustainability in the fashion world. In addition, Metsavaht is responsible for developing the concept of the New Luxury which is described as the union between the Noble and Sustainable, Ethics and Aesthetics; and aims to communicate this message through its brand and through the actions carried out jointly with some institutions, for example the Instituto-E, promoting the human sustainable development.